Avaliação nutricional de crianças com cardiopatia congênita internadas em um hospital de referência em Belém-Pa. - BATISTA, Pâmela de Oliveira (2023)
Introduction: Malnutrition in childhood causes delay in physical growth, in neuropsychomotor development, causing vulnerability to comorbidities, and this condition is considered an unfavorable risk for hospitalized children because it prolongs the hospital stay, delay in recovery and higher health care costs. Objectives: To know the nutritional status of children with congenital heart disease treated at a reference hospital in Belém, Pará. Methods: This is a descriptive, crosssectional and analytical study developed with children aged 2 to 10 years admitted to the pediatric clinic of the Hospital das Clínicas Gaspar Vianna (FHCGV), located in the metropolitan area of Belém, state of Pará. Results: The study was made up of 47 patients, of whom (53.1%) were male, most were between 6 and 10 years old 29 (61.7%). The most frequent diagnosis was Tetralogy of Fallot 9 (19.1%) followed by interventricular communication 5 (10.6%) and interatrial communication 5 (10.6%). As for nutritional status by gender, male children prevailed 17 (68.8%) and 7 (28%) were underweight. Most patients lived with father and mother 29 (61.7%), only 13 (27.6%) lived only with the mother. Most of the parents were married 19 (40.4%), followed by singles 15 (31.9%). Family income, it was possible to observe that 17 (36.1%) had an income of up to 1 minimum wage, 17 (36.1%) two or more minimum wages. Conclusion: Congenital acyanotic heart diseases prevailed, and there was a low prevalence of malnutrition among hospitalized children.